Self-Efficacy and Self-Regulated Learning’s Role in Self-Directed Learning’s Impact on Academic Writing Problem-Solving for EFL Undergraduates - Mujiono, Mujiono (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
The study examined the role of self-efficacy and self-regulated learning on the effect of self-directed learning on academic writing problem-solving for EFL undergraduates. The study applied a cross-sectional design to evaluate 213 students from the Departments of English Education and English Literature of a private university in Malang, Indonesia. Participants aged 18 to 24 years were randomly selected to ensure representative samples. This study assessed undergraduate students' writing problem-solving using custom instruments inventory of problem-solving in academic writing. Self-directed learning, self-efficacy, Â and self-regulated learning are evaluated on different scales. Methods such as confirmatory factor analysis and structural equation models are used to ensure the instrument's validity and reliability. The study found that self-directed learning had a significant impact on self-efficacy and self-regulated learning and on writing problem-solving. The study also found an important relationship between self-directed learning and the ability of EFL undergraduates to solve academic writing problems through self-efficacy and self-regulated learning. This research contributes to ongoing discussions on the relevance of self-directed learning for personal and professional development. It encourages re-evaluating educational and organizational strategies to maximize self-directed learning's benefits and minimize potential challenges.